Adolescents experience with unwanted pregnancies - Nur Fitri Ayu Pertiwi; Liza Laela Abida; Puspita Hanggit lestari (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Unwanted pregnancy in adolescents is a global problem that needs attention. The experience of adolescents after experiencing an unwanted pregnancy includes many aspects. The experience of the family in dealing with unwanted pregnancies, the experiences of the environment around adolescents related to the future of adolescents, and the experiences of adolescents in accessing health services. The aim of the study was to find out the experiences of adolescents who experienced unwanted pregnancies. The research method is scoping review using a search engine on the PubMed and Science Direct databases in the last 10 years. Based on the results of the scoping review, the theme was found: